MOJO IN TRIBUN JOGJA: A 21ST CENTURY JOURNALISM LANDSCAPE - Sukmono, Filosa Gita; Fadilla, Qholiva Yuni; Kencana, Adinda Putri Surya (Master of Communication Science Program, Universitas Diponegoro, 2022)
The launch of the Apple iPhone in 2007 marked the start of a new era in a new process for understanding the meaning of cellular communication. This gave rise to the practice of mobile journalism which uses fully mobile devices (Mojo) as the main instrument for 21st-century journalists in processing and producing an event. Especially in Indonesia, the author sees that studies on Mojo in Indonesian media are something new for academics and practitioners. The Tribune with the hashtag #MataLokalMenreachIndonesia is the only Online News Portal that has the largest regional news channel network in Indonesia that has adopted Mojo's practice in its editorial. This study explores Mojo's practice at Tribun Jogja by using a descriptive qualitative approach through interviews with related journalists. Based on the findings, the author sees that this media uses Facebook Live and the news is used as further information that will be used as news on other platforms at Tribun Jogja. With the characteristics of agile, flexibility, and accessibility, this Mojo practice can produce news with on-demand and just-in-time principles anytime, anywhere, however.